Mechanisms for redox-regulation of protein kinase C - Steinberg, Susan F. (Frontiers in Pharmacology, 2015)
Protein kinase C (PKC) is comprised of a family of signal-regulated enzymes that play pleiotropic roles in the control of many physiological and pathological responses. PKC isoforms are traditionally viewed as allosterically-activated enzymes that are recruited to membranes by growth factor receptor-generated lipid cofactors. An inherent assumption of this conventional model of PKC isoform activation is that PKCs act exclusively at membrane-delimited substrates and that PKC catalytic activity is an inherent property of each enzyme that is not altered by the activation process. This traditional model of PKC activation does not adequately explain the many well-documented actions of PKC enzymes in mitochondrial, nuclear, and cardiac sarcomeric (non-sarcolemmal) subcellular compartments. Recent studies address this dilemma by identifying stimulus-specific differences in the mechanisms for PKC isoform activation during growth factor activation versus oxidative stress. This review discusses a number of noncanonical redox-triggered mechanisms that can alter the catalytic properties and subcellular compartmentation patterns of PKC enzymes. While some redox-activated mechanisms act at structural determinants that are common to all PKCs, the redox-dependent mechanism for PKCδ activation requires Src-dependent tyrosine phosphorylation of a unique phosphorylation motif on this enzyme and is isoform specific. Since oxidative stress contributes to pathogenesis of a wide range of clinical disorders, these stimulus specific differences in the controls and consequences of PKC activation have important implications for the design and evaluation of PKC-targeted therapeutics.